1988
DOI: 10.1152/ajprenal.1988.254.2.f277
|View full text |Cite
|
Sign up to set email alerts
|

Indirect evidence of glomerular/tubular mixed-type postexercise proteinuria in healthy humans

Abstract: Hypothetical mechanisms have been postulated to explain the presence of proteins in urine after severe exercise. Recently, it has been shown that several amino acids inhibit tubular protein reabsorption. Seven healthy men, hyperhydrated, were studied during a 2-min bicycle exercise at supramaximal load. The subjects were tested without or with lysine perfusion (0.4 g/kg body wt iv). In both testing conditions, blood lactate increased to 13.8 mmol/l. Total protein urinary excretion increased to 1.10 and 1.67 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…It is useful to assess indirectly changes in glomerular membrane permeability by measuring the urine excretion rate of plasma albumin. We have provided evidence of an enhanced glomerular permeability induced by short-term strenuous exercise in young adults (8). It also appeared that postexercise proteinuria was more related to the intensity of the exercise (power output) than to its relative intensity (% of VO 2max ) (7).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is useful to assess indirectly changes in glomerular membrane permeability by measuring the urine excretion rate of plasma albumin. We have provided evidence of an enhanced glomerular permeability induced by short-term strenuous exercise in young adults (8). It also appeared that postexercise proteinuria was more related to the intensity of the exercise (power output) than to its relative intensity (% of VO 2max ) (7).…”
Section: Discussionmentioning
confidence: 72%
“…Postexercise proteinuria is more specifically related to the intensity than to the duration of the exercise (7). Moreover, the excretion of plasma proteins is due primarily to enhanced glomerular membrane permeability associated with a saturation of the reabsorption process (8). These effects, which are intensity-dependent, are transient, with return to basal state with a half-life of about 1 hour (9).…”
mentioning
confidence: 99%
“…The mechanisms postulated for glomerular proteinuria are changes in glomerular hemodynamics and in basal glomerular membrane permeability (13)(14)(15). Proteinuria disappeared after drumming in all of the individuals with RU.…”
Section: Discussionmentioning
confidence: 99%
“…however, found that there was a pattern of proteinuria suggestive of mixed glomerulo-tubular loss during an exercise test in diabetic subjects given lysine, an amino acid which blocks tubular reabsorption of filtered protein. 13 Our finding of increased albumin and transferrin excretion following exercise in the diabetic group is evidence for a glomerular leak.…”
Section: Table 2 Urinary Flow Rates and Albumin (Aer) Transferrin (mentioning
confidence: 56%